Идеи антропоцентричной лингвисти тси в трудах В.В. Виноградова - ЧЕРНУХИНА, ИННА Я. (Stylistyka, 2021)
The author fmds, in the works of V.V.Vmogradov from the '20s and '30s, some concepts that coпespond to such terms of contemporary linguistics as anthropocentric linguistics and language pe rsonality. They include, among others, the conceptions of the artistic view of the world, the type of the poetic consciousness of language, of the cultural- historical context, and, particularly, of the image of the author. In the structure of the latter concept Vinogradov distinguished three aspects: "the author's inteiltion", "the imagined personality of the writer" and "personalities of the characters".On some new types of press headlines (based on samples from the Russian press of the '80s and '90s).